Co-morbidity in women with alcohol dependence syndrome (ADS) in Eastern Nepal - Joshi, R.G.; Shakya, D.R.; Shyangwa, P.M.; Pradhan, B. (Journal of Psychiatrists’ Association of Nepal, 2017)
Introduction: Women with ADS may have psychiatric comorbidites along with physical comorbidities. Societal attitudes towards women and alcohol are barriers to the detection and treatment of their alcohol related problems. Objective: To explore the magnitude of co-morbidity among women with ADS in Eastern Nepal. Method: This is a hospital based cross-sectional study of women with ADS. Those who scored two or more than two in T-ACE questionnaire were enrolled. The diagnosis was made according to ICD-10 criteria. Consultation with concerned physician was done to assess physical condition. Result: Fifty one patients with ADS were enrolled. Among them, 21.6% had no comorbidity, 52.9% had single co-morbidity (psychiatric or physical) and 25.5% had both psychiatric and physical co-morbidity. In psychiatric comorbidity, mood disorder in 35.29% was the commonest followed by nicotine use in 26.47%. Among mood disorders 83.3% had depression. In physical comorbidity, disease of gastrointestinal tract and hepatobiliary system in 50.9% was the commonest followed by hypertension in 11.5%. Conclusion: : Psychiatric as well as physical co-morbidities are common in women with ADS. The finding points to the importance of exploring comorbidities and their optimal treatment.